2022
DOI: 10.3390/biology11030378
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Analysis for Core Networks of lncRNAs–mRNAs: Implication for Potential Role in Sterility of Crassostrea gigas

Abstract: Long noncoding RNA (lncRNA), a type of non-protein-coding transcript, is emerging as a crucial regulator of gene expression. However, few roles of lncRNA in the reproductive process of the Pacific oyster (Crassostrea gigas) have been defined, especially in the regulatory mechanism of sterile triploids gametogenesis. To uncover the potential role of lncRNA, the gonads of diploids, sterile triploids, and partially sterile triploids underwent RNA sequencing. A total of 9618 reliable lncRNAs were identified. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Here, over 88% of P. yessoensis lncRNAs were novel identified, which had no orthologs in other species. High ratio of novel lncRNAs were also found in other marine organism, for example, 98% lncRNAs identified in the spleen of the flounder ( Paralichthys olivaceus ) were unknown [ 68 ], and lncRNAs obtained in the gonad of the Pacific oyster were all novel [ 40 ]. Though the lncRNA resources in molluscs are still limited, the high ratio of unknown lncRNAs found in this study approved the view that majority of lncRNAs were short of primary sequence conservation [ 24 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, over 88% of P. yessoensis lncRNAs were novel identified, which had no orthologs in other species. High ratio of novel lncRNAs were also found in other marine organism, for example, 98% lncRNAs identified in the spleen of the flounder ( Paralichthys olivaceus ) were unknown [ 68 ], and lncRNAs obtained in the gonad of the Pacific oyster were all novel [ 40 ]. Though the lncRNA resources in molluscs are still limited, the high ratio of unknown lncRNAs found in this study approved the view that majority of lncRNAs were short of primary sequence conservation [ 24 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs exhibit crucial effects on diverse biological processes in vertebrates, such as reproduction, development, metabolism, immunity, sex determination and differentiation and so on [ 28 33 ]. With the prevalence of the next-generation sequencing, characterizations and expression patterns of lncRNAs in molluscs have been gradually investigated, and they are found functioning in diverse bioprocesses, covering immune and stress response [ 34 – 38 ], muscle growth [ 39 ], gametogenesis [ 40 ] and larval development [ 41 ]. Emerging evidence has also revealed that lncRNAs are involved in the modulation of shell biomineralization and pigmentation in molluscs [ 42 46 ].…”
Section: Introductionmentioning
confidence: 99%